Business marketing activities in Ukraine during wartime - Maxim Korneyev; Ivan Berezhniuk; Volodymyr Dzhyndzhoian; Tatiana Kubakh; Kostiantyn Horb (Innovative Marketing, 2022)
The war in Ukraine dealt a crushing blow to the country’s economy. The relevance of the topic is due to the marketing ability to be an effective tool for restoring and developing business in Ukraine. The paper aims to define the state and prospects for developing business and its marketing component during the war in Ukraine. The research analysis demonstrates that the share of business representatives who completely or partially ceased their activities during the first three months of the war decreased from 75.3% in March to 49.0% in May (compared to February 24, 2022), which is indicative of the gradual resumption of business in Ukraine. At the same time, it was found that in May 2022, the food retail, non-food retail, household appliances, and electronics sectors partially resumed their work. The best renewal rates are observed in the jewelry sector, and the worst – in the entertainment sector. A study of marketing activities in Ukraine shows that the most positive changes regarding gradual renewal are observed in digital marketing. The paper highlights the key consequences of hostilities for Ukrainian business and its marketing activities: supply chain disruption, reduced purchasing power, changes in consumer demand, stockpiling, and a state of uncertainty among business representatives. In addition, the study offers general approaches to adapting marketing and SMM during the war to preserve, restore, and further develop business in Ukraine.